2018
DOI: 10.1037/pspp0000129
|View full text |Cite
|
Sign up to set email alerts
|

Personality and behavior prediction and consistency across cultures: A multimethod study of Blacks and Whites in South Africa.

Abstract: The cross-cultural universality of behavior's consistency and predictability from personality, assumed in trait models though challenged in cultural psychological models, has usually been operationalized in terms of beliefs and perceptions, and assessed using single-instance self-reports. In a multimethod study of actual behavior across a range of situations, we examined predictability and consistency in participants from the more collectivistic Black ethnic group and the more individualistic White group in So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…The traditional collectivist notion is that they should show their loyalty to extended family members by being willing to share their income or capital by providing for the needs of a related child, including giving him or her an opportunity to receive a good education. This substantiates the findings of Fetvadjiev and colleagues (2018) and Rudwick and Posel (2014), who concluded that collectivism is still apparent in contemporary South Africa.…”
Section: Presentation and Discussion Of Research Findingssupporting
confidence: 90%
“…The traditional collectivist notion is that they should show their loyalty to extended family members by being willing to share their income or capital by providing for the needs of a related child, including giving him or her an opportunity to receive a good education. This substantiates the findings of Fetvadjiev and colleagues (2018) and Rudwick and Posel (2014), who concluded that collectivism is still apparent in contemporary South Africa.…”
Section: Presentation and Discussion Of Research Findingssupporting
confidence: 90%
“…The researchers asked the interns to record their impression management behaviours, objectives, and targets everyday for a period of 10 working days. This period of time is in keeping with the advice of Fetvadjiev, Meiring, Van de Vijver, Nel, Sekaja, and Laher (2018), who maintain that a two-week period is not uncommon for diary studies. Participants recorded their diaries in electronic (Microsoft Word) format.…”
Section: Data Collection Methodssupporting
confidence: 78%
“…The aim of this study was to ascertain the impression management strategies utilised by I/O psychology interns, at whom their strategies were directed and their goals for doing so. All the interns actively adapted their behaviours to the demands of the environment (see Fetvadjiev et al, 2018). Jones and Pittman (1982) identified five strategies used in impression management, namely intimidation, supplication, ingratiation, self-promotion and exemplification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals in collectivistic (high-context) cultures view their behavior to be more influenced by situational conditions (and less influenced by personality traits) than people in individualistic countries (Church et al, 2006). Yet, in a study involving Blacks and Whites in South Africa, Fetvadjiev et al (2018) found that cultural differences in subjective beliefs about traitedness were larger than differences in actual behavior.…”
Section: Discussionmentioning
confidence: 96%